Litterfall production and return of macronutrients of settlement in a Eucalyptus saligna (F. Muell) - Salvador, Simone Martini; Consensa, Catarine Barcellos; Araújo, Elias Frank de (Revista Ecologia e Nutrição Florestal - ENFLO, 2015)
Litterfall is the mainly route of plant nutrients transfer to the soil in forest ecosystems. Therefore the study of the litterfall is very important fundamental to understanding the functioning of these ecosystems. Given this importance, this study aimed to estimate litter production in Eucalyptus saligna stand, São Gabriel – RS. Were installed 4 plots of 23 m x 26 m in each of these plots, 4 litter collectors. For branches with a diameter bigger than 0.5 cm, in each plot were demarcated aboveground three plots of 3 m x 2 m, bounded by an average diameter tree. Samples were collected fortnightly, sorted into thick branches, twigs (diameter of less than 0.5), leaves and miscellaneous, then were oven dried, weighty, and sent to the chemical analysis where it was determinate the content of macronutrients. During the twelve month period, litter production was 9,93 Mg ha-1, 54.0% of leaves, 24.7% thick branches, 11.2% of miscellaneous and 10.1% of twigs. The overall contribution of macronutrients was 71,56 kg ha-1mof Ca, 45,15 kg ha-1 of N, 38,93 kg ha-1 of K, 17,54 kg ha-1 of Mg, 6,19 kg ha-1 of S and 2,81 kg ha-1 of P.